Analisis Kebutuhan Pengembangan Bahan Ajar IPAS Berbasis Project-Based Learning dan Edupreneurship pada Program Keahlian Kuliner di SMK - Asrorul Azizi; A. Wahab Jufri; Muhammad Sarjan; Yunita Arian Sani Anwar (Lembaga Bale Literasi, 2026)
This study investigates the need for developing integrated IPAS (Ilmu Pengetahuan Alam dan Sosial) teaching materials in vocational education, particularly within the culinary program. Addressing the gap between conceptual learning and vocational relevance, the study adopts a mixed-methods approach using a sequential explanatory design. Data were collected from nine IPAS teachers across five vocational schools in Lombok Island through a Likert-scale questionnaire and semi-structured interviews. The quantitative findings reveal that the availability and quality of existing teaching materials are low (mean = 2.11), whereas the need for Edupreneurship integration (mean = 4.33), Project Based Learning implementation (mean = 3.61), and authentic assessment development (mean = 4.67) are significantly high. Qualitative data further indicate that teachers face challenges in integrating interdisciplinary content, lack context-based instructional resources, and have not effectively linked learning to authentic culinary production processes. These findings underscore a critical mismatch between current instructional practices and the demands of vocational education. This study proposes an integrative framework of IPAS teaching materials that synergizes Project Based Learning, edupreneurship, and local culinary context to enhance students’ higher-order thinking skills and entrepreneurial competencies. This integrative approach constitutes the primary contribution of the study to vocational science education